Acute pancreatitis in end-stage renal disease patients in the USA: a nationwide, propensity score-matched analysis. Issue 8 (August 2019) - Cheungpasitporn, Wisit; Thongprayoon, Charat; Ungprasert, Patompong; Wijarnpreecha, Karn; Raimondo, Massimo; Kroner, Paul T.
Abstract : Background: Limited data exist regarding the effects of end-stage renal disease (ESRD) on acute pancreatitis (AP). This study aimed to evaluate the association between ESRD and outcomes and resource utilization of AP. Materials and methods: The 2014 National Inpatient Sample database was used to identify all hospitalized patients with a principal diagnosis of AP. Propensity score matching was performed to create a matched cohort of ESRD and non-ESRD patients. The in-hospital mortality, morbidity, resource utilization and expenditures of AP in ESRD patients were compared to non-ESRD patients. Multivariate analysis was performed for further adjustment for potential confounders. Results: Of 382 595 AP patients, 7380 ESRD patients and 8050 non-ESRD patients were created after propensity score matching. ESRD patients had more tendency to have hypercalcemia-related or AP-related to other/unspecified causes, whereas non-ESRD patients had more tendency to have alcohol-related, gallstone-related, and hypertriglyceridemia-related AP. In multivariate analysis, ESRD was associated with increased in-hospital mortality, increased length of hospital stay, and increased hospitalization costs and charges. No differences were observed in inpatient morbidity, imaging study use, and procedures performed during hospitalization. Conclusion: In this large nationwide study using inpatient USA database, we demonstrate higher AP-related mortality, and resource utilization among ESRD patients when compared with non-ESRD patients.